Occupational Health Problems, Workplace Environment and Utilization of Personal Protective Equipment among Welders of Banepa Municipality, Nepal - Joshi, Manisha; Dhakal, Gita; Shrestha, Dr. Sarala (International Journal of Occupational Safety and Health, 2020)
Introduction: Welding is a hazardous occupation where welders expose to a variety of work-related hazards. These hazards might cause occupational health problems. This study aimed to identify the prevalence of occupational health problems, workplace environment and utilization of personal protective equipment among welders. Methods: A descriptive cross-sectional study design was used for the study. Data was collected from purposively selected 130 welders of 35 metal workshops in Banepa Municipality in May-June, 2019. An observational checklist was used to collect information on the workplace environment of selected metal workshops. Data was analyzed by using Statistical Package for Social Sciences (SPSS) version 20 and described by using descriptive and inferential statistical methods. Results: The study identified that 129 welders (99.2%) experienced accidents and injuries followed by eye and ear problems (128, 98.4%). Amongst all personal protective equipment, protective goggles were available in all 35 metal workshops and insulated gloves in 25 workshops (71.4%). Similarly, 118 welders (90.6%) always used safety goggles, 53 (41%) sometimes used facemasks and 85 (65.4%) never used helmets while working. Only 9 workshops (25.7%) had first aid kits available with no expired products and 4 (11.4%) had kept fire extinguishers in easily accessible locations. Among 35, 34 workshops (97.1%) did not have safety guidelines for their workers. Conclusion: Welders who worked in metal workshops experience different types of occupational health problems (OHP) and do not use all types of PPE for their protection. Hence, metal workshops should develop safety guidelines for their workers and strictly implement them to prevent OHP.